2021
DOI: 10.1111/jonm.13478
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder in nurses in the United States: Prevalence and effect on role

Abstract: Aims:The purpose of this study is to determine the prevalence of posttraumatic stress disorder among U.S. nurses and to examine how severity of posttraumatic stress disorder symptoms are associated with their role. Background:The lifetime prevalence of posttraumatic stress disorder is estimated at 6.8%. Loss of workdays, inability to perform at full capacity, and loss of fulfillment are a few of the issues associated with an individual diagnosed with posttraumatic stress disorder. Untreated consequences includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Researchers assess that the highest-frequency selections (Connect, Family Caregivers, and COVID-19) reflect students' primary communication concerns: building connections with patients and families and navigating the exceptional communication demands during pandemic peaks. These patterns align with research identifying the desire to build trusting human connections in nursing clinical practice, 22 family as a key communication concern for nurses, 23 and COVID-19 as a depleting communication phenomenon for nurse providers. 24 Student narratives advocated for using and integrating the resource in courses and clinicals.…”
Section: Team Identifies Communication Labor In Teams Recognizes Chal...supporting
confidence: 69%
“…Researchers assess that the highest-frequency selections (Connect, Family Caregivers, and COVID-19) reflect students' primary communication concerns: building connections with patients and families and navigating the exceptional communication demands during pandemic peaks. These patterns align with research identifying the desire to build trusting human connections in nursing clinical practice, 22 family as a key communication concern for nurses, 23 and COVID-19 as a depleting communication phenomenon for nurse providers. 24 Student narratives advocated for using and integrating the resource in courses and clinicals.…”
Section: Team Identifies Communication Labor In Teams Recognizes Chal...supporting
confidence: 69%
“…Especially at the beginning of the pandemic, HCWs may have felt worried about infecting their loved ones, may have been afraid of the disease, felt stigmatized and isolated by society, suffered traumatic experiences and ethical dilemmas, and may have been subjected to high levels of stress, anxiety, and depression ( 20 , 21 ). In addition, in the work environment, many HCWs have lacked personal protective equipment, have had increased patient load, have had to make difficult decisions, have witnessed a high number of deaths of patients under their care, have been forced to double shifts, and have been relocated from their services ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…It should not be disregarded that suicidal ideation is a predictor of future suicide attempts and suicide deaths ( 26 ), hence the importance of addressing it at early stages. In this regard, Sahimi et al ( 27 ) and Rodney et al ( 21 ) found that 17% of physicians reported suicidal ideation, of whom 1% had attempted suicide. Furthermore, HCWs are more likely than non-HCWs to succeed in suicide attempts as they have greater access to more lethal drugs and have knowledge about the sufficient dosage to end their lives ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review (Schuster & Dwyer, 2020) reported that 8.5%–20.8% of nurses met the diagnostic criteria for PTSD, highlighting its prevalence among nurses. PTSD causes significant impairment in attention to detail, task prioritization, and concentration in nurses, leading to a more negative perception of colleagues, avoidance of work‐related tasks, increased desire to leave their profession, and increased risk of suicide (Rodney et al., 2022).…”
Section: Introductionmentioning
confidence: 99%